Development and validation of a nomogram to predict intraoperative blood transfusion for gastric cancer surgery. Issue 4 (20th April 2021) - Huang, Haoquan; Cao, Minghui
Abstract: Objective: To construct and validate a nomogram composed of preoperative variables to predict intraoperative blood transfusion for gastric cancer surgery. Background: Intraoperative transfusion for gastric cancer surgery is a common medical procedure that is associated with increased postoperative complications. Methods: A total of 999 patients who underwent gastrectomy between January 2010 and June 2019 were randomly allocated into the primary and validation cohorts in a 2:1 ratio. In the primary cohort, logistic analyses were performed to identify independent predictors for transfusion. Using the Akaike information criterion, selected variables were incorporated to construct a nomogram. Validations of the nomogram were performed in the primary and validation cohorts. The discrimination ability of the nomogram was assessed by the concordance index (C‐index), and calibration was assessed by calibration curves and the Hosmer–Lemeshow goodness‐of‐fit test. Results: The following risk factors for transfusion were identified and used to construct the nomogram: ASA status (III‐IV vs I‐II: odds ratio [OR] 1.74), comorbidities (yes vs no: OR 1.57), tumour location (diffuse vs lower: OR 4.05), cTNM stage (III vs I: OR 1.95), and a preoperative haemoglobin level less than 80 g/L (vs over 120 g/L: OR 35.30). The C‐index was 0.859 and 0.850 in the primary and validation cohorts, respectively, which both indicated good discrimination of the nomogram. Additionally, both calibration curves and Hosmer–Lemeshow tests ( p ‐value 0.184 and 0.887, respectively) demonstrated high agreement between the predictions and actual outcomes. Conclusion: A nomogram composed of preoperative variables to predict blood transfusion for gastric cancer surgery was effectively developed and validated. This nomogram could be used to improve the utilisation of red blood cells for gastrectomy.